Probiotics as an Adjuvant for Management of Gastrointestinal Cancers through their Anti-inflammatory Effects: A Mechanistic Review - Javid, Hossein; Karimi-Shahri, Mehdi; Khorramdel, Malihe; Mashhad, Alireza S.; Tabrizi, Ayda T.; Sathyapalan, Thozhukat; Afshari, Amir R.; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2023)
The immune system's role in maintaining the health of the gastrointestinal (GI) system is like a double-edged sword. Simultaneously, it could reduce the risk of pathogen invasion by the inflammatory response. However, if regulated improperly, it could also propagate oncogenic signaling that transfers a normal cell into the malignant counterpart. Thus, several mechanisms have been proposed, such as the immune system could disturb the GI homeostasis and increase the survival and proliferative capacity of cells, leading to the formation of a wide range of malignancies. Among the endless list of these mechanisms, inflammatory responses are currently fascinating research areas, as this response regulation is by the gut microbiota. Given this, microbiota manipulation might be a convenient and efficient way to prevent GI cancer. Probiotics could potentially achieve this by overturning the milieu in favor of normal gut homeostasis. In addition to the safety of the use of probiotics, along with their potential ability to interact with immune system responses, these bacteria are also being analyzed from the perspective of dietary supplements. In the present review, we aimed to look into the mechanisms through which probiotics modulate immune response to stimulate anti-inflammatory responses and promote immune surveillance against neoplastic cells.
Keywords: colorectal cancer